Table of Content - - (Journal of Islamic Sciences, 2025)
:Table of Content • The attitude of the People of the Book on Abrogation, and the Responses of Qur’anic Commentators: A comparative study Ms. Roaa Hameed Alyoubi, Prof. Sulaiman Qasim Al-Eid • Jurisprudence of verses from the book of Al-Hawi by Imam Al-Mawardi (deceased in 450 HA) Breastfeeding book (Collection and Study) Ms. Maryam Saad Al-Safari • The Ruling on Implementing Retribution Between Male and Female: A Comparative Jurisprudential Study under Omani Law Mr. Ali Said Ali Ghafram Alshahri, Mr. Ahmed Mohammed Ali Ghafram Alshahri • The Recitation of Imam Abu Mujliz Al-Sudusi (d. circa 101 AH): A Compilation and Analytical Study Asst. Prof. Muhammad Omar Majeed • Jizya in the modern state Mr. Ahmed Fathi Abdel-Azim • Semantic Potential in the Legal Meanings of Revealed Texts: An Analytical Reading of Its Inference Effects within Islamic Thought Dr. Fazry Hamza